Management of Pediatric Cataract with Acrylic Foldable Intraocular Lens: Our Experience - Rashid, Riffat; Hassan, Md Jafrul; Afzal, Farzan; Alam, Shovona; Ahmed, Jamal Nizamuddin; Huq, Deen Mohd. Noorul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: In Bangladesh, one-third (31%) of childhood blindness are from cataract. The management of which remains a challenge; treatment is often difficult, tedious and requires a dedicated team effort. The study was done to observe the postoperative visual acuity and complication following implantation of foldable acrylic hydrophobic intraocular lens (IOL). Methods: This prospective study was done during the period of July 2006 to June 2011. This study comprised of patients in the age group of 216 years with unilateral and bilateral, congenital and developmental cataract, who underwent cataract surgery and implantation of foldable acrylic hydrophobic IOL. They were followed up at day 1, day 7, 1 month, 6 months and 1 year after operation to assess the incidence of posterior capsular opacity (PCO) and occurrence of postoperative complications. Results: Thirty-eight eyes of 30 pediatric patients underwent cataract surgery and underwent acrylic foldable IOL implantation. Postoperative anterior chamber reaction was minimum and the incidence of PCO was 18.32%. But, no severe PCO developed. Other complications like pupillary capture and decentration of IOL was also absent. Conclusions: It can be concluded that foldable acrylic hydrophobic IOL is well tolerated in the pediatric eye. There is less chance of postoperative inflammation and development of PCO. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.23 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 25-29